Impact of financial leverage on firm profitability evidence from non-financial firms listed in colombo stock exchange- sri lanka - Ravindran, M.; Kengatharan, L. (University of Jaffna, 2021)
Purpose: The aim of this research is to find out the impact of financial leverage on firm profitability of the listed non-financial firms in Sri Lanka. Design/Methodology/Approach: Total of 290 companies listed on Colombo Stock Exchange (CSE) is considered as the population and the sampling process excluded Banking, Finance, and Insurance companies as they have identical financial characteristics. The study analyzed 82 non-financial firms listed in CSE from year 2013 to 2017. Debt to equity ratio and liquidity were considered as independent variable. Further, sales growth and firm size were considered as control variables. Return on assets of the firm measures the profitability of the firms and incorporated as dependent variable. The study used panel regression analysis, descriptive tests, and correlation analysis. Findings: Fixed effect model reveals that there is a negative significant impact of financial leverage on return on assets of the non-financial firms listed in CSE. The study elaborates a high influence on return on assets due to the independent variables considered in the study since the R2 value becomes 85.43%. Originality: The review of the literature reveals that there are limited number of studies have been carried out incorporating all the non-financial firms in recent past considering the time period of 2013 - 2017. Therefore, this study would provide more insights including the firms’ performance during these periods. Further, it was identified that there are contradictions in the previous findings. Therefore, the study provides more insights to examine the performance of non-financial firms due to the incorporation of debt capital during the period of 2013 – 2017. Theoretical and Policy implications: M&M 1963, agency cost theories are providing the arguments over the mix of debt-to-equity proportion in the organizational capital structure. This study considers the non-financial firm’s performance according to its capital structure. This can be justified that the operational structure of financial and non-financial firms is significantly different. Therefore, the capital structure incorporation would provide significantly different impacts in between financial and non-financial firms. Therefore, the study adds more value by analyzing only the performance of non financial firms based on its financial leverage. Research limitations/ Future research directions: The study uses only the secondary data and the five year period from 2013 – 2017. Future studies can be done increasing the sample size and employing different methods such as case studies, that would provide more insights to the findings of this study.
Keywords: Financial leverage; Return on assets; Debt to equity ratio; Fixed effect model; Non-financial firms listed under CSE